"I Do": Does Marital Status Affect How Much CEOs "Do"?. Issue 1 (January 2015) - Nicolosi, Gina; Yore, Adam S.
Abstract This paper explores whether a CEO's marital status reveals unobservable risk preferences which influence their firm's investment and compensation policies. Using biographical data for CEOs of large domestic companies, we find that corporate deal‐making activity (e.g., mergers, joint ventures, major capital expenditures, etc.) and overall firm riskiness both increase significantly with personal life restructuring (e.g., marriages and divorces). This relation is supported by an instrumental variables analysis and also an investigation surrounding CEO turnover. Finally, the link between a CEO's marital status and preference for option‐based compensation further suggests that personal restructuring may be an indicator of executive risk appetites.